Analisis Faktor yang Berhubungan dengan Kejadian Dismenorhea - Sadiman, Sadiman (Jurnal Kesehatan, 2017)
Dismenorhea cause women can’t doing activity normally and need medicine. That situation make quality life of women decreased. Incident rate of primary dismenorhea in Indonesia is 54,89%, while the rest is dismenorhea secondary type. Preface study showed that 63% students at Metro Midwifery Study Program had dismenorhea (47 students of 74 student), and from 47 students that ever experience the dismenorhea, there were 9% (4 students) who not join to lecture because dismenorhea. This study was to know factors that have correlation with dismenorhea. It was an analytic study with case control design. Population were all of students of Metro Midwifery Study Program, total were 280 students. Sample of this study was determined by Lemeshow formula. Total of Case samples were as same as control samples, each had 53 students. Sampling technique was random sampling. Incident analysis of dismenorhea were used chi square with α=0,05, there were no correlation between menarche age and dismenorhea (p-value=0,301). There were correlation of family history and long menstruation with dismenorhea (p-value=0,032 and 0,000). Effort to decrease dismenorhea pain, students need to applied health lifestyle like doing physical exercise regularly, fulfill balance nutrition, not consume caffeine beverage and more consumtion water.